The relevance of compartmentation for cysteine synthesis in phototrophic organisms - Birke, Hannah; Wirtz, Markus; Hell, Rüdiger (Protoplasma, 2012)
In the vascular plant Arabidopsis thaliana, synthesis of cysteine and its precursors O-acetylserine and sulfide is distributed between the cytosol, chloroplasts, and mitochondria. This compartmentation contributes to regulation of cysteine synthesis. In contrast to Arabidopsis, cysteine synthesis is exclusively restricted to chloroplasts in the unicellular green alga Chlamydomonas reinhardtii. Thus, the question arises, whether specification of compartmentation was driven by multicellularity and specified organs and tissues. The moss Physcomitrella patens colonizes land but is still characterized by a simple morphology compared to vascular plants. It was therefore used as model organism to study evolution of compartmented cysteine synthesis. The presence of O-acetylserine(thiol)lyase (OAS-TL) proteins, which catalyze the final step of cysteine synthesis, in different compartments was applied as criterion. Purification and characterization of native OAS-TL proteins demonstrated the presence of five OAS-TL protein species encoded by two genes in Physcomitrella. At least one of the gene products is dual targeted to plastids and cytosol, as shown by combination of GFP fusion localization studies, purification of chloroplasts, and identification of N termini from native proteins. The bulk of OAS-TL protein is targeted to plastids, whereas there is no evidence for a mitochondrial OAS-TL isoform and only a minor part of OAS-TL protein is localized in the cytosol. This demonstrates that subcellular diversification of cysteine synthesis is already initialized in Physcomitrella but appears to gain relevance later during evolution of vascular plants.